IoT-Enabled Automatic Sugar Filling Device with Weight-Based Control - Fadel Muhammad; Iskandar Lutfi; A. Rahman, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
In the era of Industry 4.0, efficiency and automation in production processes have become essential, particularly in the food sector. Manual sugar filling processes have several limitations, such as inaccurate measurements and reliance on human labor. Therefore, this study developed an automated sugar filling system based on the Internet of Things (IoT) with selectable doses of 500 grams, and 1 kilogram. The system is designed using an ESP32 microcontroller, a load cell sensor integrated with the HX711 module, servo and DC motors, as well as infrared and ultrasonic sensors. The device’s data can be monitored in real time via the Blynk application on a mobile device. Testing results show that the system is capable of automatically dispensing sugar with high accuracy and can notify users when the sugar stock in the hopper is low. This system is expected to enhance the efficiency and effectiveness of sugar filling processes, particularly for small-scale industries or household applications.